THE CHOICE OF STRATEGY FOR INNOVATIVE SECURITY DEVELOPMENT OF ENTERPRISES - NYZHNYK, OLEG; NYZHNYK, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
Determining an effective strategy for innovative security development of enterprises is the main task of their operation in modern business conditions, taking into account the existing risks of such activities. The basis of functioning and selection and formation of the strategy of innovative security development is the general strategy of the enterprise, which strategy should have a comprehensive action plan of the enterprise, which will ensure the implementation of its mission and goals and be focused on improving its long-term effectiveness. The task of innovation strategies at a certain level is not only to establish the competitive advantage of the enterprise in goods and markets, but also to maintain a competitive advantage and ensure economic security. The article analyzes the existing strategies for innovative development of small and medium enterprises. The security component of such development is defined, the importance of observing the level of economic security of development of small and medium business enterprises is emphasized. The basic forms of strategic planning of innovative safe development of small and medium business enterprises are offered. Competitive strategies are closely related to the efficient use of available and potential resources and provide for customer satisfaction by gaining market leadership. The introduction of certain management technologies in the development and selection of a strategy for innovative security development of small and medium-sized businesses will build a certain algorithm of actions that can affect the level of their innovative development and economic security. The analysis of scientific views on the problems of choosing enterprise development strategies allowed to identify real approaches to finding factors influencing the level of innovative development and the level of their economic security, to determine the components of developing a strategy for innovative security development of enterprises and to offer existing management technologies. small and medium enterprises.